Evaluation of a Proposal for Movement Integration in the Teaching–Learning Process in Early Childhood Education - Nielsen-Rodríguez, Adriana; Romance-García, Ángel Ramón; Dobado-Castañeda, Juan Carlos; Gil-Espinosa, Francisco Javier (IOAP-MPDI, 2022)
Physical activity is essential to child development, but studies show that children are increasingly inactive. Due to schools being considered privileged environments to promote physical activity, the aim of this study was to increase the physical activity performed by early childhood education children during the school day by integrating movement into academic content and analyze this process. The amount and intensity of physical activity performed by a group of 24 3–4-year-old children in three different weeks were measured by accelerometry: one week with the methodology they had been following (week 1); and two weeks in which movement was integrated into the content through a specific proposal (week 2) and the same improved proposal (week 3). The results reveal that the application of a movement integration program not only allowed students to work on academic content in a physically active way, but also significantly increased the amount of physical activity that children performed during the school day. However, it was necessary to carry out several interventions the same day, or make movement integration the reference methodology, to meet the minimum recommended physical activity levels. In addition, to increase their effectiveness, interventions should be continually reviewed and improved to increase the motor engagement time.
Keywords: Educación de la primera infancia; Early childhood education; Physical activity; Movement integration; Active methodologies; Active learning; Accelerometry